ISOLAMENTO E CARACTERIZAÇÃO DE MICRORGANISMOS FOTOSSINTETIZANTES ASSOCIADOS A LIQUENS - SOUSA, Daniele Pereira de Oliveira (2022)
Lichen constitutes some of the oldest and most diverse symbionts on Earth. They are defined as organisms that, through a symbiotic association between fungi (mycobiont) and unicellular algae and/or cyanobacteria (photobiont), originate a stable vegetative body, with its own structure, physiology and ecology, called lichen thallus. Their importance lies in the fact that they have high biotechnological potential, thanks to their numerous secondary metabolites with varied activities with medical and therapeutic properties; and due to their extreme sensitivity to environmental pollutants, they are, for this reason, commonly used in environmental biomonitoring studies. Furthermore, the study of photosynthesizing microorganisms as lichen symbionts, although still very scarce, provides subsidies for the reconstruction of evolutionary histories and a better understanding of how the interaction occurs in these associations. In the state of Maranhão, precisely on the island of São Luís, there are still no reports of studies involving the lichenic community. Thus, it is assumed that no survey has yet been carried out in this area, and therefore this is the first study of the lichenized microbiota in this region. Therefore, the present study was concerned with making a survey on the lichen community, as it corresponds to a subject with great global relevance through the speed at which environments are changing, since they can be used as sentinels in the monitoring of environmental changes; and the fact that they are very promising as a source of biomolecules, which gives them great economic importance, since these biomolecules may eventually result in the production and synthesis of possible new drugs and treatments against diseases. To this end, two studies were developed involving an integrative format review and an unprecedented study that sampled lichenized fungi and their lichen microbiota on São Luís Island. The first chapter consisted of a review of scientific studies published in the last two decades on cyanolichens, which showed on the one hand how little this group of organisms is still discussed and known and on the other hand how important they are in the synthesis of bioproducts and how biomonitors of environmental and atmospheric pollution. The second chapter described the composition of lichen photobionts and served to help in the initial survey of lichen microflora on São Luís Island. The results of this study emphasize the need for further studies on the subject and corroborate the important role that the lichen community plays for the environment and human health.